O "direito vivo" das liminares: um estudo pragmático sobre os pressupostos para sua concessão - Costa, Eduardo José da Fonseca (2009)
As far as the matter of granting injunctive relief is concerned there is a dead right provided in state-approved legal texts that is in disagreement with the living right of forensic practice. When ruling on the granting of urgent injunctions, the plain wording in the legislative text may give rise to an interpretation whereby the fumus boni iuris and the periculum in mora are requirements independent of each other. As a result, for the traditional scholastic doctrine which usually conforms to chiefly analytic and hermeneutic dogmatic models the absence of either one or the other of these requirements suffices to have the motion for preliminary injunction denied [= rigid and mechanistic model]. However, an empirical study of the status of the legal practice shows that justices usually take together the fumus boni iuris and the periculum in mora and that those requirements seem to have a mutually complementary relationship. In other words: a dogmatic-pragmatic model can through empiric, descriptive and inductive investigative procedures prove that in daily court practice the absence or the lean presence of one of the requirements may from time to time be offset by the exaggerated presence of the other [= fluid and adaptive model]. This is why in daily court practice it is possible to find orders granting preliminary injunctions grounded (α) merely on a near certainty of the allegation of a material right to which the plaintiff claims to be entitled, with the justice leaving out of consideration the presence of the periculum in mora [= plain extreme evidence injunction], or (β) only on the imminent danger of extreme irreparable harm, with the justice leaving out of consideration the presence of the fumus boni iuris [= plain extreme urgency injunction]. In this sense, the several types of preliminary injunction are but points of tension tugging at the strands of a rope stretched between the fumus boni iuris and the periculum in mora. The more the tension moves toward the fumus boni iuris the closer it gets to the granting of extreme evidence injunction; the more the tension moves toward the periculum in mora the closer it gets to the granting of extreme urgency injunction. Halfway between these extremes lies an infinitesimal set of possibilities all interlinked by means of a vital connection. Thus, within this infinitude eight key-types of preliminary injunction stand out: a) plain extreme evidence injunction; b) plain extreme urgency injunction; c) extreme evidence and non-extreme urgency injunction; d) extreme urgency and non-extreme evidence injunction; e) extreme evidence and extreme urgency injunction; f) non-extreme evidence and non-extreme urgency injunction; g) presumed extreme plain evidence injunction; h) presumed extreme plain urgency injunction. Therefore, it is naïve to maintain that the granting of preliminary injunctions is either a discretionary (Cândido Rangel Dinamarco), or an associative (Betina Rizzato Lara) act. As a matter of fact, it does have something of a discretionary and something of an associative quality, since it is an act of complex conditionality, an outcome of a justice s appraisal of the fundamental tension between the fumus boni iuris and the periculum in mora such as they appear in a given real case